French queer cinema - Rees-Roberts, Nick (Edinburgh University Press, 2008)
French Queer Cinema looks at queer self-representation in contemporary auteur film and experimental video in France. Whilst there is growing research on representations of queer sexualities in France, this is the first comprehensive study of the cultural formation and critical reception of contemporary queer film and video. French Queer Cinema addresses the socio-political context informing both queer DIY video and independent gay cinema, including films such as Patrice ChÃ♭reau's Ceux qui m'aiment prendront le train, Olivier Ducastel and Jacques Martineau's DrÃþle de FÃ♭lix, FranÃʹois Ozon's Le Temps qui reste and AndrÃ♭ TÃ♭chinÃ♭'s Les TÃ♭moins. Taking up the recent Anglo-American attention to queer migration, the book looks at gay fantasies of Arab (beur) men, as well as beur self-representation in Europe's fastest-selling gay DV porn production CitÃ♭beur. Further chapters cover transgender dissent, and the effects of AIDS and loss on the formation of gay identities. Key Features Provides a full, up-to-date account of the formation, reception and setting for contemporary queer film and video in France. Situates cinematic representations of migration, social exclusion and queer sexualities in the context of recent repressive legislation on sex work and immigration. Covers the work of less well-known directors such as Christophe HonorÃ♭, SÃ♭bastien Lifshitz and Gañl Morel.